Law in the laboratory a guide to the ethics of federally funded science research - Charrow, Robert (Chicago, Ill. : University of Chicago Press, 2010)
This title provides an introduction to the major ethical and legal considerations pertaining to research under the aegis of federal science funding. For any academic whose position is grant funded, or for any faculty involved in securing grants this book will be an essential reference manual.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Research -- Moral and ethical aspects; Research -- Law and legislation; Science -- Research grants -- Handbooks, manuals, etc; Bioethics; Society; United States of America, USA; Social law & Medical law; Science: general issues; Industrial applications of scientific research & technological i; Science funding & policy